2019
DOI: 10.1111/ijcp.13433
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicines for asthma in children and adults: A systematic review of placebo‐controlled studies

Abstract: Background Traditional medicines (TMs) adjunctive to conventional medications are widely used for asthma in east‐Asia and have gained popularity in western countries. Objective To assess the efficacy and safety of TMs for asthma in children and adults based on placebo‐controlled trials in order to inform physicians and assist them in discussions with patients. Methods Seventeen electronic databases were searched. Participants had acute or chronic asthma. Interventions included orally administered traditional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(230 reference statements)
0
1
0
Order By: Relevance
“…Dulla and Jahan 70 indicated that some traditional Chinese medicines indicated their effectiveness against asthma in children when compared to modern medicines such as salbutamol and montelukast. In another research, some of the traditional herbal medicines in East-Asia were used as adjuncts in improving acute and chronic asthma outcomes 85 which boosts the evaluation of TMPs for clinical trials. Wang et al 86 reported that the clinical efficacy of traditional Chinese medicine, which binds to proteins, are potential targets for asthma therapy.…”
Section: Anti-asthmatic Potential Of Tmps Against Ova-induced Asthma In Animalsmentioning
confidence: 99%
“…Dulla and Jahan 70 indicated that some traditional Chinese medicines indicated their effectiveness against asthma in children when compared to modern medicines such as salbutamol and montelukast. In another research, some of the traditional herbal medicines in East-Asia were used as adjuncts in improving acute and chronic asthma outcomes 85 which boosts the evaluation of TMPs for clinical trials. Wang et al 86 reported that the clinical efficacy of traditional Chinese medicine, which binds to proteins, are potential targets for asthma therapy.…”
Section: Anti-asthmatic Potential Of Tmps Against Ova-induced Asthma In Animalsmentioning
confidence: 99%